Antimicrobial activity of negative air ions - Sioson, Jesse Dave DL (University of the Philippines Diliman, 2007)
ABSTRACT The antimicrobial effect of negative air ions (NAI) was examined in this study. Acrylic vinyl plastic was selected as the material for the NAI chamber assembly for its non-conductivity, non-breakability, moldability, and transparency. Two NAI chamber, each constructed to accommodate one negative ion generator (NIG) in its core, were designed and fabricated to include a ventilation system for smooth airflow in mobilizing NAIs, and a core for the NAI treatment. A comparative analysis between an open system (NIG set on an open space) and a closed system (NIG inside the NAI chamber), showed the efficiency of generating NAIs of 1023 V in the closed system at a distance of 10 cm between the NIG electrode and the ion counter, at 0.2 m/s air velocity, 5-minute exposure time, and 5kV applied voltage. Measurements of the amount of NAI generated at various applied voltages revealed the highest reading of 2.95 kV at 12 kV applied voltage. The amount of NAI generated and the applied voltage are related linearly (r = 0.9813). Continuous exposure of streak-plated Aspergillus niger to NAIs for 72 hours at 37°C revealed that NAI treatment did not prevent mold growth. Continuous exposure of spread-plated spores of A. niger to NAIs for the same duration and temperature resulted in 27.6% mean reduction (equivalent to 0.14 log10 reduction) in mold growth compared to the inoculated, unexposed plates. Paired t-test at p = 0.01 indicated that NAI treatment significantly inhibited A. niger.